Studies of the chemistry of plasmas used for semiconductor etching - Toogood, M; M. J. Toogood (1991)
﻿ Optical diagnostic techniques have been developed and then used to investigate the chemistry of reactive species formed in CF4 / O2 rf parallel plate discharges, similar to those employed in semiconductor material processing. Oxygen atoms were detected by two photon laser induced fluorescence (LIF), and the technique was found to have a number of experimental caveats owing mainly to the high laser intensities required. In particular, amplified spontaneous emission (ASE), was observed from laser excitation of oxygen, and was found to influence the spontaneous fluorescence signal and thus question the use of LIF for ground state concentration measurements in these systems. The spin orbit states of the 3p 3P level were resolved for the first time, both in using high resolution excitation experiments and also as a consequence of detecting ASE. Spin orbit temperatures of less than 50° above ambient were observed. The absolute concentration of oxygen has been found to be 7.4 ± 1.4 x 1013 cm-3 in a 50 mTorr, 100 W, 85% O2 / CF4 plasma. Optical emission was also used to study fluorine atoms and to examine the use of the actinometered emission technique as a measure of ground state concentrations. The latter was investigated directly by comparison with LIF measurements of O and CF2, and in many cases shown to be a poor representation of the ground state concentration. To investigate the chemical and physical processes in the plasma, time resolved methods are required and a new technique, time resolved actinometry, has been developed, tested by comparison with LIF measurements and then used to study the kinetics of fluorine atoms. Results have shown the importance of wall reaction rates on the magnitude of the fluorine atom concentrations, and the sensitivity of these concentrations to the nature of the surface, particularly in the presence of oxygen and silicon. Oxygen has also been shown to be removed predominantly at the surface but the influence of gas phase reactions with CFx radicals is apparent in discharges containing low percentages of O2. Studies on an afterglow type, electron cyclotron resonance reactor have been carried out as a comparison to the parallel plate system, and high excitation and dissociation levels have been observed from differences in the emission intensities and from measured values of the absolute CF and CF2 concentrations. The use of LIF as a diagnostic for CF has been investigated by probing the predissociation of the A2Σ+ state. Emission from the A2Σ+ (v = 2) level has been seen for the first time, and a J independent predissociation mechanism, with a rate of 3 x 109 s-1 has been observed.